A Multistage Chi-square Test for Measurement of the Degree of Association in Two-way Table. Issue 4 (20th April 2016) - Zhu, Jianping; Fang, Kuangnan
Abstract : The classical chi-square test for independence cannot convey additional information and the degree of the association of two factors in two-way contingency table. Besides, measures of association by contingency coefficient need to be used with care, because the association measures depend on the number of rows r and the number of columns c. This article proposes a multistage chi-square test to measure the degree of the association between the two factors in two-way contingency table. We also give simulation and real examples to assess the performance of the proposed method. The results show that our proposed method can effectively investigate the degree of association of two factors in two-way contingency table.